"Standing humbly in the ante-chambers of Clio": the rise and fall of Union War Histories - Grey, Jeffrey (Scientia Militaria - South African Journal of Military Studies, 2012)
The Second World War was a titanic struggle which involved the Dominions of the ’old’ Commonwealth in the British and allied war effort from the war’s very beginning. Each Dominion took a different role in the war - Australia alone was heavily involved in the Pacific war against the Japanese, for example, while Canadians, New Zealanders and South Africans all fought in the European Theatre of Operations, and New Zealanders and South Africans fought in the Western desert as well - and the domestic reactions and pressures on national governments likewise differed in each case. Homogeneous Anglo-Celtic societies in Australia and New Zealand experienced few internal rifts over the fact of involvement in the war, while in both Canada and South Africa the politics of divergent linguistic communities restricted the options available to national governments when it came to decisions governing their national contributions to a ’British’ war effort. In the war’s aftermath the place which the war had occupied in national life was by turns, solidified, contested, appropriated by different groups in a manner similar to that which had occurred after the First World War, and with some of the same outcomes.